COLONIAL AMBIVALENCE AND LAL BEHARI DAY’S CONCERN WITH FOLK TALES - Halder, Deb Dulal; Sharma, Shrawan K (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Lal Behari Day’s collection of folktales from Bengal was the first printed book of folk narratives from Bengal. Its impact on later collections of Bengali folktales has been substantial. Richard Carnac Temple’s suggestion to assemble such an edition occasioned the compilation of these tales. However, the distinctive ambivalences in Lal Behari’s collection of tales stem from his unique identity as a native Christian preacher. The paper “Colonial Ambivalence and Lal Behari Day’s Concern with Folk Tales” examines Lal Behari Day’s defying and evading conventions, specifically how they relate to the dominant narratives that moulded Bengali colonial discourse and Day’s writings.